2016
DOI: 10.15578/jpbkp.v11i1.284
|View full text |Cite
|
Sign up to set email alerts
|

Isolasi dan Karakterisasi Parsial Kolagen dari Teripang Gamma (Stichopus variegatus)

Abstract: Isolasi dan karakterisasi parsial kolagen dari teripang gamma (Stichopus variegatus) telah dilakukan. Isolasi dilakukan melalui tiga tahap yaitu preparasi, ekstraksi dan isolasi. Tahap preparasi meliputi tahapan penyiangan, pencucian dan perendaman dalam akuades, dalam alkohol, dalam larutan Tris-HCl dan etilenadiaminatetraasetat  (EDTA) dan perendaman dalam larutan natrium hidroksida (NaOH). Ekstraksi dilakukan dengan perendaman asam asetat 0,5M. Isolasi dilakukan dengan cara pengendapan menggunakan NaCl dila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 17 publications
0
6
0
6
Order By: Relevance
“…reported. This result was used as a preliminary data for non-alcohol pre-treatment in the collagen extraction to remove fat instead of those conducted by Fawzya et al (2016) and Nagai, Tanoue, Kai, and Suzuki (2015). The moisture, ash, protein and fat contents of Stichopus varied from 90.86 to 95.14; 31.69 to 56.12; 30.73 to 54.32 and 1.46 to 4.89%, respectively.…”
Section: Chemical Composition Of Sea Cucumber and Yield Of Collagenmentioning
confidence: 99%
See 1 more Smart Citation
“…reported. This result was used as a preliminary data for non-alcohol pre-treatment in the collagen extraction to remove fat instead of those conducted by Fawzya et al (2016) and Nagai, Tanoue, Kai, and Suzuki (2015). The moisture, ash, protein and fat contents of Stichopus varied from 90.86 to 95.14; 31.69 to 56.12; 30.73 to 54.32 and 1.46 to 4.89%, respectively.…”
Section: Chemical Composition Of Sea Cucumber and Yield Of Collagenmentioning
confidence: 99%
“…Research on the biological activity of sea cucumbers from Nusa Tenggara have been reported, including radical scavenging activity of ethanolic extract of Holothuria leucospilota, H. atra, H. fuscocinerea, and H. excellens (Pangestuti et al, 2016), -glucosidase inhibition of methanolic extract of S.hermanni (Mariyanti, 2017), and tyrosinase inhibitor activity of S. hermanni collagen (Safithri et al, 2018). Other explorations of golden sea cucumber or gamat (S. hermanni or S. variegatus) from various locations that have been published were studies on collagen extraction (Alhana, Suptijah, & Tarman, 2015;Fawzya, Chasanah, Poernomo, & Khirzin, 2016), sulfated glycosaminoglycan content (Masre, Yip, Sirajudeen, & Ghazali, 2010), angiotensin-I-converting enzyme (ACE) inhibitor and antioxidant activity of collagen peptide (Khirzin et al, 2015), the potential of S. hermanii to improve the growth of stem cells (Arundina, Suardita, Setiabudi, & Ariani, 2016), the effect of sea cucumber extract on the lymphocytes numbers of Wistar rat's oral mucus during the healing process from a traumatic ulcer (Arundina, Yuliati, Soesilawati, Damaiyanti, & Maharani, 2015); the growth-promoting effect of S. variegatus its water extract to boost the proliferation of spinal astrocytes (Patar, Jamalullail, Jaafar, & Abdullah, 2012) and the ability of sulfated glycosaminoglycan from S. hermanni integument in the process of wound healing (Masre et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Warna kolagen disebabkan oleh pigmen dari bahan baku dan selain itu, warna kolagen dapat disebabkan oleh metode isolasi yang digunakan. Menurut Fawzya et al (2016) metode kolagen larut asam dapat memberikan warna kolagen yang lebih putih dibandingkan dengan dengan menggunakan metode hidroekstraksi, karena penggunaan konsentrasi asam yang lebih tinggi dibandingkan dengan metode hidro-ekstraksi. Perendaman dengan menggunakan basa atau asam menyebabkan pengembangan pada kulit sehingga pigmen dapat dieliminasi (Jaswir et al 2011) .…”
Section: Karakter Fisikokimia Kolagen Kulit Ikan Parang Parangunclassified
“…Glisin terdapat pada posisi ketiga susunan asam amino tripel heliks kolagen (Gly-X-Y). Posisi X adalah prolin dan posisi Y adalah hidroksiprolin yang akan membentuk triple heliks (Fawzya et al 2016). Berdasarkan hasil analisis kolagen kulit ikan parang parang memiliki kadar asam amino glisin yaitu 26,69 % dan hampir menempati sepertiga dari jumlah asam amino.…”
Section: Asam Amino Kolagenunclassified
See 1 more Smart Citation